Hematological variables of the Pêga donkey (Equus asinus) breed: influence of age and sex - Girardi, Annita Morais [UNESP]; Marques, Luiz Carlos [UNESP]; de Toledo, Carmen Zilda Pereira [UNESP]; de Campos Filho, Eugênio [UNESP] (Springer Nature, 2015)
Appropriate hematological reference intervals mitigate the risk of unnecessary investigations and failures on disease diagnosis. Species, breed, environment, handling, and physiologic stage could influence hematological variables. In this context, there is a lack of hematological reference intervals for Pêga donkeys, an important Brazilian asinine breed. This study aimed to establish hematological reference values for Pêga donkeys and determine the influence of age and sex on these variables. The complete blood count of samples collected from 110 animals, 79 females and 31 males was performed, maintained under field conditions. The animals under 1 year old (three females and five males) were monitored by collections on the day of birth, on 3rd, 7th, 15th day, and monthly until 12 months of life, while the other donkeys were sampled once. There were differences in several variables analyzed, confirming the requirement of different reference intervals according to age group and sex. Moreover, differences among the values obtained and those of previous studies show a breed influence on the hematological variables of donkeys. For Pêga breed donkeys, animal’s age and sex influence most of the hematological variables. This study can be useful in the clinical routine and serve as basis to other scientific researches related to Pêga donkeys.
Keywords: Asinine; Clinical pathology; Hematology; Pêga; Reference intervals